Lessons Learned in Implementing Patient-Reported Outcome Measures (PROMs) in the Australian Breast Device Registry (ABDR). (17th December 2020) - Ng, Sze; Parker, Emily; Pusic, Andrea; Farrell, Gillian; Moore, Colin; Elder, Elisabeth; Cooter, Rodney D; McNeil, John; Hopper, Ingrid
Abstract: Background: The Australian Breast Device Registry (ABDR) is a clinical quality registry which utilizes both surgical data and patient-reported outcome measures (PROMs) to understand device performance. The ABDR is the first national breast device registry utilizing the BREAST-Q Implant Surveillance module to conduct PROMs via text messaging as the primary method of contact for most patients. ABDR PROMs are structured upon a successful acceptability and feasibility study and a pilot study. Objectives: This aim of this paper was to examine the challenges we faced and consider how lessons learned in implementing PROMs might inform future registry studies and interventions. Methods: We tracked the number of completed follow-ups and documented feedback between October 2017 and December 2018 from various stakeholders, including sites, surgeons, and patients. Results: In total, 10, 617 patients were contacted: 59% of breast augmentation and 77% breast reconstruction patients responded to our PROMs survey. We encountered challenges and developed solutions to overcome several key issues, including database setup; follow-up contact methods; ethics; education of surgeons and patients; associated costs; and ongoing evaluation and modification. The strategies we devised to address these challenges included drawing on experiences from previous studies, greater communication with sites and surgeons, and having the flexibility to improve and modify our PROMs. Conclusions: The ABDR PROMs experience and lessons learned can inform a growing number of registries seeking to conduct PROMs. We describe our approach, obstacles encountered, and strategies to increase patient participation. As more breast device registries worldwide adopt PROMs, data harmonization is crucial to better understand patient outcomes and device performance.